SISTEM PENDETEKSI DINI KEBOCORAN GAS BERBASIS IOT DENGAN KONEKSI KE WEB SERVER - Muhammad Fahrul Anam; Firman Hadi Sukma Pratama (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2025)
Gas leaks in domestic and commercial environments pose a threat to human safety and assets. This research presents the design and implementation of an innovative gas leak detection system, the G2D (Gas Detection Device), using the MQ2 gas sensor. The NodeMCU microcontroller acts as the brain of the system to capture, process, and transmit gas detection data via the Internet of Things (IoT) connection. The main feature of this system is the implementation of real-time communication through a server, enabling quick responses to gas leak threats. The integration of IoT and the server allows for remote access and control, enhancing flexibility in security monitoring. Testing was conducted by simulating various gas leak scenarios, demonstrating performance in detecting and providing notifications via the Web Server. The G2D gas leak detection system has the potential to improve daily safety through the efficient use of MQ2 sensors, IoT, and Web Server communication.